Automação de subestação: uma análise do processo de modernização de uma subestação 500 kV – Eletrobras/Eletronorte - OLIVEIRA, Bartolomeu do Vale (2023)
The present work presents an analysis of the modernization process of a 500 kV Substation of ELETROBRAS/ELETRONORTE, located in the city of Tucuruí-PA, addressing the architecture of the Protection, Control, and Supervision System, as well as the technology used in the substation automation, such as intelligent electronic devices (digital relays). For that, the case study method was used, with data collection and bibliographical research. Finally, from the information obtained, it was possible to understand the entire modernization process, going through its conception, development, and implementation phases, and, even more relevant, the main advantages were verified, concerning conventional systems, obtained in various areas such as operation, maintenance, engineering, and safety. The modernization of the Tucuruí 500kV Substation ensured a significant improvement in the performance, reliability, and safety of the system, in addition to reducing costs and increasing stability, meeting the requirements of the electricity sector.